The Social Capital of Religious Harmony: A Study of Desa Sadar Kerukunan in Ilir Kota, Sanggau Regency, West Kalimantan - Fitriyanto, Andry; Kurniawan, Syamsul; Fatimah, Lisyati (Religió Jurnal Studi Agama-agama, 2024)
This article investigates the relationships between two congregations, Muslims and Confucians, of two places of worship, that is, Al-Ikhlas Mosque and Tri Dharma Temple adjacent to each other in Desa Sadar Kerukunan, Ilir Kota, Sanggau Regency, West Kalimantan. These two places of worship together arguably form the icon of tolerance between religious communities. To ensure that a society characterized by religious and ethnic diversity is harmonious, social capital is necessary to bolster the cohesiveness of relationships between individuals and groups. This study is field research with a qualitative approach and a descriptive method. Employing Robert D. Putnam’s theory of social capital encompassing trust, norms, and networks, this study found that firstly, the deep trust of each religious community is well fostered, which is reflected in the practice of inter-religious communities helping each other. Secondly, there are social networks established and preserved by the elite of the two places of worship. Thirdly, social norms encourage all activities related to ethnicity and religious identity to be communicated clearly to all parties. Fourthly, harmony between religious communities around these two places of worship is driven by the same motive to preserve a common interest, that is, the economic aspect.